Health system factors associated with post-trauma mortality at the prehospital care level in Africa: a scoping review. Issue 1 (30th September 2020) - Koome, Gilbert; Atela, Martin; Thuita, Faith; Egondi, Thaddaeus
Abstract : Background: Africa accounts forabout 90% of the global trauma burden. Mapping evidence on health systemfactors associated with post-trauma mortality is essential in definingpre-hospital care research priorities and mitigation of the burden. The studyaimed to map and synthesize existing evidence and research gaps on healthsystem factors associated with post-trauma mortality at the pre-hospital carelevel in Africa. Methods: A scoping review of published studies and grey literature was conducted. The search strategy utilized electronic databases comprising of Medline, Google Scholar, Pub-Med, Hinari and Cochrane Library. Screening and extraction of eligible studies was done independently and in duplicate. Results: A total of 782 study titles and or abstracts were screened. Of these, 32 underwent full text review. Out of the 32, 17 met the inclusion criteria for final review. The majority of studies were literature reviews (24%) and retrospective studies (23%). Retrospective and qualitative studies comprised 6% of the included studies, systematic reviews (6%), cross-sectional studies (17%), Delphi studies (6%), panel reviews (6%) and qualitative studies (12%), systematic reviews (6%), cross-sectional studies (17%), Delphi studies (6%), panel reviews (6%) and qualitative studies (12%). Reported post-trauma mortality ranged from 13% in Ghana to 40% in Nigeria. Reported preventable mortality is as high as 70% in South Africa, 60% in Ghana and 40% in Nigeria. Transport mode is the most studied health system factor (reported in 76% of the papers). Only two studies (12%) included access to pre-hospital care interventions aspects, nine studies (53%) included care providers aspects and three studies (18%) included aspects of referral pathways. The types of transport mode and referral pathway are the only factors significantly associated with post-trauma mortality, though the findings were mixed. None of the included studies reported significant associations between pre-hospital care interventions, care providers and post-trauma mortality. Discussion: Although research on health system factors and its influence on post-trauma mortality at the pre-hospital care level in Africa are limited, anecdotal evidence suggests that access to pre-hospital care interventions, the level of provider skills and referral pathways are important determinants of mortality outcomes. The strength of their influence will require well designed studies that could incorporate mixed method approaches. Moreover, similar reviews incorporating other LMICs are also warranted. Key Words: Health System Factors, Emergency Medical Services [EMS], Pre-hospital Care, Post-Trauma mortality, Africa.